A therapy pup to reunite them - DaRosa, Luana (Harlequin medical romance, 2023)
Reunited with her first love! Setting up a charity matching therapy dogs with patients in need is Dr. Raquel's calling. Her career took a back seat for too long and she can't afford to be distracted. Enter hotshot neurosurgeon Christian--her brother's best friend and her teenage crush!--who's looking for a pup for his niece. The tension between them is as unchanged as it is undeniable... Will one night to get things out of their systems solve all their problems?